EVALUATION OF DIURETIC ACTIVITY OF AQUEOUS EXTRACT OF BOERHAAVIA DIFFUSA ROOTS IN RATS - SUDHA MADHURI; VISHAL KALASKER; RAMBHIMAIAH; SREEKANTHA (International Journal of Pharma and Bio Sciences, 2013)
The roots and leaves of Boerhaavia diffusa were used in ayurveda as a diuretic. The present study is aimed at evaluating the diuretic effect of aqueous extract of Boerhaavia diffusa roots.Aqueous extract of Boerhaavia diffusa was administered to experimental rats orally at the doses of 300mg/kg, frusemide 10mg / kg was used as a standard. Normal saline 25ml / kg was used as a control in study. The diuretic effect of the extract was evaluated by measuring urine volume, sodium, potassium and chloride content by electrolyte analyzer.Urine volume was significantly (P < 0.0001) increased by aqueous extract in comparison to control group, excretion of Na, K & Cl was also significantly (P < 0.0001) increased. The diuretic effect of the extract was comparable to that of the reference standard.Aqueous extract of Boerhaavia diffusa produces a notable diuretic effect which appears to be comparable to that produced by reference diuretic frusemide. The study provides a quantitative basis for explaining the folkloric use of Boerhaavia diffusa.